The human liver matrisome – Proteomic analysis of native and fibrotic human liver extracellular matrices for organ engineering approaches. (October 2020) - Daneshgar, Assal; Klein, Oliver; Nebrich, Grit; Weinhart, Marie; Tang, Peter; Arnold, Alexander; Ullah, Imran; Pohl, Julian; Moosburner, Simon; Raschzok, Nathanael; Strücker, Benjamin; Bahra, Marcus; et al.
Abstract: The production of biomaterials that endow significant morphogenic and microenvironmental cues for the constitution of cell integration and regeneration remains a key challenge in the successful implementation of functional organ replacements. Despite the vast development in the production of biological and architecturally native matrices, the complex compositions and pivotal figures by which the human matrisome mediates many of its essential functions are yet to be defined. Here we present a thorough analysis of the native human liver proteomic landscape using decellularization and defatting protocols to create extracellular matrix scaffolds of natural origin that can further be used in both bottom-up and top-down approaches in tissue engineering based organ replacements. Furthermore, by analyzing human liver extracellular matrices in different stages of fibrosis and cirrhosis, we have identified distinct attributes of these tissues that could potentially be exploited therapeutically and thus require further investigation. The general experimental pipeline presented in this study is applicable to any type of tissue and can be widely used for different approaches in regenerative medicine and in the construction of novel biomaterials for organ engineering approaches.